The Concept of Multi-track Diplomacy in Indonesian Coast Guard to Strengthen the International Maritime Relationship - Sean Narahara; Lukman Yudho Prakoso; Rudi Sutanto (Journal of Political Issues)
Indonesia is one of the largest archipelagic countries in the world with vast stretches of ocean. The pillars in the effort to defend Indonesia's seas are not only found in the TNI, but also in the coast guard. Bakamla as Indonesia's coast guard is tasked with protecting the country's oceans, however Bakamla faces many problems. This problem is in the form of a shortage of personnel, and is also Bakamla's main step in becoming part of Indonesia's maritime defense strategy. This research was created using a qualitative approach and literature review methods to reach the right solution to solve this problem. The results of this research include that Bakamla has a crucial role in law enforcement in Indonesia's maritime areas and also has a major responsibility for the security of the nation and state from the maritime sector. Bakamla also has the rights and opportunities to implement the precise trinity roles that is implemented in the navy since both of them serve the similar roles. As an advancement of this those roles, Bakamla also has the rights to implement the use of Multi-track Diplomacy concept to strengthen its function in international diplomacy with other country in order to reduce or even avoid the tension that has been the main issues of current era. Therefore, it is hoped that Bakamla can apply the concept of multi-track diplomacy within the naval trinity concept further, so that Indonesia's maritime defense can increase.